2009
DOI: 10.1017/s0021932009990046
|View full text |Cite
|
Sign up to set email alerts
|

Wife Abuse in Rural Bangladesh

Abstract: Intimate partner violence (IPV) is a global public health and gender problem, especially in low-income countries. The study focused on verbal abuse, physical abuse and abuse by restricting food provision to wives by their husbands by victim and perpetrator characteristics, emphasizing the socioeconomic context of rural Bangladesh. Using a cross-sectional household survey of 4411 randomly selected married women of reproductive age, the study found that a majority of the respondents are exposed to verbal abuse (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
101
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(122 citation statements)
references
References 21 publications
(29 reference statements)
14
101
1
6
Order By: Relevance
“…Different studies showed that the relationship between individual educational attainment and intimate partner violence and sexual violence was complex. Low level of education was however the most consistent factor associated with both the perpetration and experiencing of intimate partner violence and sexual violence across studies (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Women who reported lower levels of education (primary or none) had a 2 to 5-fold increased risk of intimate partner violence compared to higher-educated women ( 14,15,19, 23 24,25,26 ).…”
Section: Discussionmentioning
confidence: 92%
“…Different studies showed that the relationship between individual educational attainment and intimate partner violence and sexual violence was complex. Low level of education was however the most consistent factor associated with both the perpetration and experiencing of intimate partner violence and sexual violence across studies (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Women who reported lower levels of education (primary or none) had a 2 to 5-fold increased risk of intimate partner violence compared to higher-educated women ( 14,15,19, 23 24,25,26 ).…”
Section: Discussionmentioning
confidence: 92%
“…Despite copious research evidence pointing to men as perpetrators of wife beating, most studies examine risk factors that render women vulnerable to their husbands [2,4 -6]. Information is usually indirectly obtained from the women, even for studies exploring characteristics of male batterers [1][2][3]7]. There is a paucity of literature on studying males as perpetrators of wife abuse.…”
mentioning
confidence: 99%
“…Wife beating is an acute issue in the Indian subcontinent [7][8][9][10]. However, few studies have examined men's attitudes toward wife beating, especially in that region [2,3,6,10 -14] A study on Indian men's attitudes toward violence against women indicates that men's relationship rights and autonomy are highly predictive of wife beating, especially for those men who have been exposed to parental violence during childhood [3].…”
mentioning
confidence: 99%
“…In addition, IPV was associated with a higher number of children. Rahman et al [37] conducted a study in Bangladesh that mirrors this finding.They found Muslim women to be significantly more likely to experience unintended pregnancies than non-Muslim women. However, a study by Dalalet al [34] on contraception use and IPV targeting both Muslim and non-Muslim women in Bangladesh found that abused women are twice as likely to use contraceptives.…”
Section: Ipv and Associated Health Issuesmentioning
confidence: 74%
“…Three studies conducted in Bangladesh identified that Muslim women were more likely to experience all forms of IPV than their non-Muslim counterparts [34][35][36]. However, a fourth study by Dalalet al [37] found the same differences between Muslim and non-Muslim women in all forms of abuse except for physical abuse. Contrary to the findings of the Bangladeshi studies, research conducted with Lebanese women found Armenian women in the study cohort reporting more physical abuse than Muslim women [38].…”
Section: Prevalence and Types Of Abusementioning
confidence: 99%